Mengokohkan Otoritas Mufassir Melalui Uá¹£Å«l al-TafsÄ«r (Review Kitab â€˜Ilm al-TafsÄ«r: Uá¹£Å«luhÅ« wa ManÄhijuhÅ« karya Muhammad Afifuddin Dimyati) - Ahmad Syaifuddin Amin (UIN Siber Syekh Nurjati Cirebon, 2021)
The delaying of uá¹£Å«l al-tafsÄ«r study in the world causes its stagnancy in Indonesia. Muhammad Afif Dimyathi as a productive scholar presented his work entitled â€œilm al-tafsÄ«r: Uá¹£Å«luhÅ« wa ManÄhijuhu as to answer the need of uá¹£Å«l al-tafsÄ«r literature in Indonesia especially for Islamic universities. Containing 14 chapters, This book could systematically present some representative objects of uá¹£Å«l al-tafsÄ«r study such as basic discussion of tafseer, methodology , trend and some rules of Qurâ€™anic exegesis. By Afifuddinâ€™s work, uá¹£Å«l al-tafsÄ«r can be presented as simple and systematic object although in terms of content, He was still repeating objects discussed by other previous scholars. The affirmation of tafseerâ€™s authority is a main character ofÂ his tought arising from traditionalist culture.